2017
DOI: 10.1111/jar.12359
|View full text |Cite
|
Sign up to set email alerts
|

Community football teams for people with intellectual disabilities in secure settings: “They take you off the ward, it was like a nice day, and then you get like medals at the end”

Abstract: The psychosocial benefits of organised community sports programmes far outweigh the physical health benefits. Careful consideration must be given to where on a treatment and rehabilitation pathway non-traditional therapeutic interventions such as sports programmes are offered as an adjunct to specific risk reduction interventions for people with LD in secure settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…It was not stated what the weekly physical activities consisted of in that study, but the limited participation could indicate that the content was not suitable for the FMU. In contrast, a study on people with intellectual disabilities in secure settings implemented community football successfully (Hudson et al., 2018). In that study, the participants reported substantial psychosocial benefits besides the physiological effects.…”
Section: Discussionmentioning
confidence: 99%
“…It was not stated what the weekly physical activities consisted of in that study, but the limited participation could indicate that the content was not suitable for the FMU. In contrast, a study on people with intellectual disabilities in secure settings implemented community football successfully (Hudson et al., 2018). In that study, the participants reported substantial psychosocial benefits besides the physiological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Research in disability sport has emerged over the past decade with several studies investigating the benefits, [14][15][16][17] barriers, [15][16][17][18][19][20][21][22] facilitators [19][20][21][22][23] and motivations 24 for sport participation across a range of ages, impairments and performance levels. Specifically in Paralympians, studies have examined athletic identity, [26][27][28] retirement, 29 injury experiences 30 and the barriers and facilitators to participation in elite sport.…”
Section: Open Accessmentioning
confidence: 99%
“…-12 papers were excluded as they did not include any quantitative estimates of mental disorders, such papers dealt with the use of football to improve mental health in different groups including spectators, soccer fans and patient groups, that is, subjects with schizophrenia or learning disability (e.g. Hudson et al 2017). The majority of these studies were experience reports of different football-related projects without quantitative data.…”
Section: Mental Health In Professional Football Players and Refereesmentioning
confidence: 99%